Continuous phenol biodegradation in a simple packed bed bioreactor of calcium alginate-immobilized Candida tropicalis (NCIM 3556) - Varma, R. J.; Gaikwad, B. G. (World Journal of Microbiology & Biotechnology, 2010)
Phenol biodegradation in a continuous system of immobilized Candida tropicalis NCIM 3556 was studied. The bioreactor was simple, it had a feed inlet from the bottom and the effluent outlet from top, no supplementary oxygen was supplied, the reactor was operated continuously for 116 days. Initially the column was run continuously with a feed concentration of 2 g l(-1) for 42 days whence a degradation of > 97% was achieved. The feed concentration was then increased to 3 g l(-1), for which a similar to 80% biodegradation was sustained for 90 days after which there was a steady decrease in the performance. When the phenol degradation was reduced to similar to 50% in 116 days, the reactor was stopped. The efficiency of free cells recycled every 24 h and immobilized cells were compared; it was estimated that repeated reuse of free cells in batch mode gave an overall efficiency of 0.102 g phenol degradation g(-1) cell wet weight in 12 days. In contrast, the immobilized system of the same biomass had a longer working lifetime of similar to 4 months indicating an efficiency of 3.72 g phenol g(-1) cell wet wt.
Keywords: Biodegradation; Ca alginate; Candida tropicalis; Immobilization; phenol